GROUP PRESENTATION IN NON-ENGLISH DEPARTMENT CLASSES: INVESTIGATING STUDENTS’ MOTIVATION, ANXIETY, AND EXPERIENCE - Amelia, Rizky; Amelia, Rini; Muhammad Isa (UHN IGB Sugriwa Denpasar, 2025)
English in vocational higher education is a compulsory subject in semester 1. In dealing with future career needs, presentation is provided in the Semester Learning Plan. In this study, students worked in groups to deliver presentations. This study aims to explore students' perceptions of learning English in presentation material by describing students' motivation, anxiety, and experiences. The researchers used a qualitative descriptive method. The participants of the study were all first-semester students at the Politeknik Negeri Banjarmasin who voluntarily responded to the questionnaire (79 students) and seven students who would represent those to be interviewed. The research instruments are a fifty-item question through Google Form and an interview guide for data triangulation. The results of this study showed that, in general, the students perceived group presentation positively. They have a very positive perception of motivation and a positive perception of presentation experience, although they are also anxious when preparing and delivering the presentation. The use of a project in the group presentation helped students collaborate, enhanced their motivation, and facilitated student-centered learning. Speaking anxiety of students was influenced by internal factors such as nervousness, which can interfere with supporting devices and situations in the classroom. All in all, students perceived positively the implementation of the presentation project to finish the presentation. The result of this research study is expected to be used in teaching and learning in the field of learning English as a foreign language and to encourage students to be more motivated and less anxious so that their speaking performance is better.